Effect Of Tax Avoidance, Profitability, Liquidity And Company Size On The Value Of The Company (Empirical Study On Property And Real Estate Sector Companies Listed On The Indonesia Stock Exchange In 2020-2023) - Lilis Puspasari; Muhammad Abdul Aris (SEAN Institute, 2024)
The value of the company describes the well-being of the company's management and shareholders, the higher the value of the company, the better the company's performance in the eyes of investors. This study aims to determine the influence effect of tax avoidance, profitability, liquidity and company size on the value of the company. This study is included in the category of quantitative research. The Data used is secondary data. The population used in determining the sample of this study is the property and real estate sector companies listed on the Indonesia Stock Exchange in 2020-2023. Sampling techniques in this study using purposive sampling techniques, and obtained a final sample of 42 companies. The method of data collection using documentation with data analysis techniques using classical assumption test, multiple regression analysis, coefficient of determination, t test, and F test. The results of this study showed that tax avoidance, profitability, and company size affect the value of the company, while liquidity does not affect the value of the company.